2019
DOI: 10.7150/ijms.24068
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide promoted proliferation and adipogenesis of preadipocytes through JAK/STAT and AMPK-regulated cPLA2 expression

Abstract: The proliferation and adipogenesis of preadipocytes played important roles in the development of adipose tissue and contributed much to the processes of obesity. On the other hand, lipopolysaccharide (LPS), also known as endotoxin, is a key outer membrane component of gram-negative bacteria in the gut microbiota, and has a dominant role in linking inflammation to high-fat diet-induced metabolic syndrome. Studies suggested the potential roles of LPS in hepatic steatosis and in obese mice models. However, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…LPS stimulates the proliferation of pre-adipocytes through a CD14-dependent mechanism 205 , possibly through activation of JAK/ STAT and AMPK via cytosolic phospholipase A2 (reF. 206 ).…”
Section: Role Of Gut Dysbiosis and Inflammationmentioning
confidence: 99%
“…LPS stimulates the proliferation of pre-adipocytes through a CD14-dependent mechanism 205 , possibly through activation of JAK/ STAT and AMPK via cytosolic phospholipase A2 (reF. 206 ).…”
Section: Role Of Gut Dysbiosis and Inflammationmentioning
confidence: 99%
“…Previous studies indicated that LPS could promote the proliferation in several cell types . However, whether LPS stimulate or inhibit and /or did not affect the proliferation of the cells may depend on the cell type and LPS itself, as well as concentrations of LPS.…”
Section: Discussionmentioning
confidence: 97%
“…However, whether LPS stimulate or inhibit and /or did not affect the proliferation of the cells may depend on the cell type and LPS itself, as well as concentrations of LPS. Recent study showed that LPS (1 μg/mL) had no impact on the viability of ovarian granulosa cells in buffalo, while LPS (20 μg/mL) enhanced the proliferation of preadipocytes, and LPS increased the number of sertoli cells in a dose‐dependent way (0.1‐100 μg/mL) . Studies also have showed that LPS from Porphyromonas gingivalis at 10 μg/mL increased periodontal ligament cells proliferation, but LPS from E. coli reduced the proliferation in this cell type .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was abrogated by inhibition of either EGF receptor (EGFR) or STAT3 expression, revealing a role for EGF-mediated STAT activation both in delaying senescence of ASCs, and in enhancing their adipogenic potential [20]. Lipopolysaccharide (LPS) and tumor necrosis factor alpha (TNFα), two mediators known to contribute to obesity-related inflammation, both induce the expression of cytosolic phospholipase A2 (cPLA2) through activation of JAK2/STAT3/STAT5 signaling in various cell types [21][22][23]. It has also been shown that cPLA2 induces adipogenesis [24].…”
Section: Adipogenesismentioning
confidence: 99%